FRI0564 PSTPIP1- ASSOCIATED MYELOID-RELATED PROTEINEMIA INFLAMMATORY SYNDROME/PAMI SYNDROME: CASE REPORT AND REVIEW OF THE LITERATURE. (June 2019) - Mejbri, Manel; Theodoropoulou, Katerina; Hofer, Michael
Abstract : Background: PAMI syndrome is a recently described condition, previously known as Hyperzincemia/Hypercalprotectinemia (Hz/Hc) syndrome. It is a very rare auto-inflammatory disorder characterized by a chronic systemic inflammation, cutaneous and osteo-articular manifestations, hepatosplenomegaly, anemia and neutropenia. Increased blood levels of MRP 8/14 (S100A8/A9 or calprotectin) and zinc distinguish this condition. Specific pathogenic mutations in PSTPIP1 gene (p.E250K and p.E257K) were identified as the genetic cause of this condition. Objectives: Case presentation and review of literature Case Presentation: We report a case of 13 months age female referred to our unity for recurrent episodes of osteoarthritis. Physical examination showed hepatosplenomegaly. Blood work revealed a systemic inflammation, a microcytic anemia and neutropenia. A complete workup for metabolic disorders, oncologic processes and uncommon infections was negative. Because of history of recurrent osteoarthritis, a whole-body MRI was performed and confirmed a multifocal osteomyelitis. Whole exome sequencing identified the missense p.E250K in the PSTPIP1 gene. Methods: A literature search on PAMI syndrome was performed until the15 October 2018. Pubmed was screened using a combination of the following terms: Hyperzincemia, Hypercalprotectinemia, E250K mutation, PSTPIP1 mutation, PAPA with E250K mutation. Results: We identified 20 cases of PAMI syndrome in the literature. PAMI syndrome is an early onset inflammatory disease with a median age of 2.4 years. Clinical manifestations include Osteo-articular manifestations (80%), skin lesions (71%), splenomegaly (89%), hepatomegaly (68%), lymphadenopathy (42%), growth failure (58%) and hemorragic diasthesis with recurrent epistaxis and/or haematoma tendency in 5 patients. All cases had relevant abnormalities in hematologic parameters: mild to severe neutropenia and anemia (100%). Thrombocytopenia (42%). Systemic inflammation was confirmed in 94% using the monitoring of CRP, ESR or SAA. Zinc and MRP 8/14 blood concentrations were markedly elevated in all tested patients. Genetic analyses of PSTPIP1 gene revealed the two specific identified mutations (p.E250K and p.E257K) in all patients. Response to the treatment was variable with no consistently effective therapy. Most common therapeutic options were AINS, Corticosteroids (n=9), Anakinra (n=9), Anti-TNF (n=6) and Cyclosporine A (n=4). Conclusion: PAMI syndrome is a rare auto inflammatory condition which should be considered in patients with undefined systemic inflammation and neutropenia, even without skin or osteo-articular manifestations. Zinc and serum MRP 14/8 measurement may be helpful tools for the diagnostic orientation in these cases. References: [1] HOLZINGER D, FASSL SK, de JAGER D, et al.: Single amino acid charge switch defines clinically distinct proline-serine-threonine phosphatase- interacting protein 1 (PSTPIP1)- associated inflammatory diseases. [2] E. BELELLI, C.PASSARELLI, M.PARDEO, et al: Haematological involvement associated with a mild autoinflammatory phenotype, in two patients carrying the E250K mutation of PSTPIP1 [3] SAMAN K. HASHIMI, KATIE BERGSTROM, ALISON A BERTUCH, et al: PSTPIP1-associatedmyeloid-related proteinemia inflammatory syndrome: A rare cause of childhood neutropenia associated with systemic inflammation and hyperzincemia [4] SAMPSON B, FAGERHOL MK, SUNDERKOTTER C, et al.: Hyperzincemia and hypercalprotectinemia: a new disorder of zinc metabolism. [5] FESSATOU S, FAGERHOL MK, ROTH J, et al.: Severe anemia and neutropenia associated with hyperzincemia and hypercalprotectinemia. Disclosure of Interests: Manel Mejbri: None declared, Katerina Theodoropoulou: None declared, michael hofer Grant/research support from: novartis, SOBI, Consultant for: Novartis, SOBI